Caring for the elderly in a controlled environment : a practical guide for caregivers and guardians - Niles, Joyce (The Author St. ThomasBB, 2012)
Describes different ways of caring for the elderly. Supports learned elder care skills, helps to improve techniques in efficiency, provides caregivers with commonsense communication methods that promote listening rather than telling, and guiding rather than directing or preaching. It empowers caregivers with knowledge-based skills that can help reduce the demands for care of the elderly on today's over-burdened public health care system.